Stres pada korban dating violence usia dewasa awal: bagaimana peran dukungan sosial? - Anjar Hayuning; Tatik Meiyuntaringsih; Akta Ririn Aristawati (INNER: Journal of Psychological Research, 2023)
Abstract Stress is a condition caused by differences in a person or environment related to an individual, namely between the desired situation and the biological, psychological, or social system of the individual. One of the factors that influence stress levels in individuals is the social support provided by the environment to individuals with the aim of making individuals feel valuable, loved, and cared for by their environment. The purpose of this research is to find out whether there is a negative relationship between social support and stress in victims of dating violence. The subjects in this study were early adults with an age range 18-25 years wh had experiencd dating violence. The sampling technique iin this study used a purposive sampling technique with the criteria described when distributing the data. The number of samples in this study were 50 people. In data analysis using the Pearson Product Moment parametric correlation technique. The result obtained were 0,661 with a significance value of p=0,000, where p<0,01. This means that the hypothesis which states that there is a negative relatonship between social support and stress in victims of dating vilolence is rejected. Keywords: Stress, Social support, Early adults, Dating violence.